The effects of tidal modulation of breaking wave in a macrotidal beach in the Amazon coast (Ajuruteua-PA): climatic patterns and unplanned territorial occupation - COSTA, Remo Luan Pereira Marinho da (2022)
The objective of this study was to know the effects of tidal modulation of breaking waves in a recreational macrotidal beach on the Amazonian coastline, considering different climatic patterns. The study was divided in two approaches, one with medium-term data series (2006-2018) acquired by National and International institutions, and other with in situ short-term data of tides and waves at Ajuruteua beach between 2012 and 2014. Images obtained by Digital globe were extracted using Google Earth (GE) software. These images were used to monitor the coastline in different periods (05/06/2007, 28/04/2013 and 07/09/2021) in the study area. Offshore forces - winds and waves - blew from northeasterly to southeasterly (45°<θ< 120°N) during most of the study period, Severe storms in 2007, 2009, 2011 and 2017 with average and gust wind speeds above 20 m s-1, coinciding with the La Niña event. During the same period, Hos were above 5 m associated with periods of 16 to 23s. Riverine discharges also were related to rainfall levels with extremes ranges recorded during climatic events, such as those of 2008-2009 (La Niña), 2010 (El Niño and Drought), 2011 (La Niña), 2012-2013 (Drought) and 2015-2016 (El Niño). Nearshore wave heights and periods were modulated by the semi-diurnal tidal fluctuation and variability depends of offshore condition and local climate. A progressive beach retreat was recorded along of that coastline. Comparing 2007 with 2021, it was possible to register a reduction of 0.15 km2 and a beach retreat of 0.360 km in the most northern part of Ajuruteua beach. Unplanned territorial occupation and the lack of beach planning have intensified the erosive processes in this macrotidal beach that expect waves of moderate energy. Coastal planning and regulation is urgently required for the study area. Given this, this study suggests that the governmental authorities must control the local territorial occupation, as well as must consider physical processes from short to long term for the future contention projects.